Kasabach‐Merritt‐like syndrome in a dog secondary to isolated splenic haemangiomatosis. Issue 2 (7th June 2020) - Pazzi, Paolo; Clift, Sarah; Hartman, Marthinus Jacobus; O'Dell, Nicolize
Abstract : A 13‐year‐old intact male miniature schnauzer presented with lethargy, distended abdomen and pallor. Pancytopenia was identified on complete blood count with a severe thrombocytopenia. Cavitatory severe splenomegaly was identified on abdominal ultrasound. Two weeks of immunosuppressive therapy had no effect on the thrombocytopenia and a splenectomy was performed. The platelet count returned to normal within 24 hours of splenectomy. Isolated splenic haemangiomatosis was confirmed on histopathology and immunohistochemistry. The anaemia and severe thrombocytopenia in conjunction with the ultrasound findings and histopathology are characteristic of Kasabach‐Merritt syndrome in people. This is the first case of Kasabach‐Merritt‐like syndrome described in the dog.